Utilizing Virtual Reality to Understand Athletic Performance and Underlying Sensorimotor Processing - Kimura, T.; Nasu, D.; Kashino, M. (Proceedings, 2018)
In behavioral sports sciences, knowledge of athletic performance and underlying sensorimotor processing remains limited, because most data is obtained in the laboratory. In laboratory experiments we can strictly control the measurement conditions, but the action we can target may be limited and differ from actual sporting action. Thus, the obtained data is potentially unrealistic. We propose using virtual reality (VR) technology to compensate for the lack of actual reality. We have developed a head mounted display (HMD)-based VR system for application to baseball batting where the user can experience hitting a pitch in a virtual baseball stadium. The batter and the bat movements are measured using nine-axis inertial sensors attached to various parts of the body and bat, and they are represented by a virtual avatar in real time. The pitched balls are depicted by computer graphics based on previously recorded ball trajectories and are thrown in time with the motion of a pitcher avatar based on simultaneously recorded motion capture data. The ball bounces depending on its interaction with the bat. In a preliminary measurement where the VR system was combined with measurement equipment we found some differences between the behavioral and physiological data (i.e., the body movements and respiration) of experts and beginners and between the types of pitches during virtual batting. This VR system with a sufficiently real visual experience will provide novel findings as regards athletic performance that were formerly hard to obtain and allow us to elucidate their sensorimotor processing in detail.